РОЗПОДІЛЕНЕ РЕГУЛЮВАННЯ НАПРУГИ РОЗПОДІЛЬЧОЇ ЕЛЕКТРОМЕРЕЖІ З ВІДНОВЛЮВАНИМИ ДЖЕРЕЛАМИ ЕЛЕКТРОЕНЕРГІЇ - Блінов, І.В.; Трач, І.В.; Рибіна, О.Б. (Інститут електродинаміки Національної академії наук України, 2023)
The problems of distributed voltage control in electrical grids (EGs) with renewable sources of electric energy with  converter-interfaced generation (CIG) . It is proposed to control the EGs modes by controlling the reactive power of converter-interfaced generation. It is proposed to use the mean square deviation of the voltage in the converter interfaced generation (CIG) installation nodes as the criterion of the target function. The extremum seeking control  method  was used to solve the problem of dynamic optimization with daily changes in the parameters of the electric network, namely the loads and active power of renewable sources. The examples provided have shown the improvement of the voltage in the EG at different  levels of reactive power generation limitation according to the norms of the standard EN50549-1:2019. The optimal values ​​of the average daily value of the rms deviation of the voltage of the ieee33 test EM were obtained with a significant penetration of the RES power. Bibl.13.